Sustainability and agriculture in the “mezcal region” of Oaxaca - Bautista, Juan Antonio; Smit, Mascha A. (Revista Mexicana de Ciencias Agrícolas, 2018)
This study analyzes agricultural systems in hillsides and valleys, developed by peasant producers of Agave angustifolia Haw. It was done in the “mezcal region” located in the Central Valleys of Oaxaca, 2009. The objectivewastoidentifysustainableagriculturalpractices in the production of agave. It is said that, knowledge and traditional peasant farming practices contribute to environmental and productive sustainability. Based on the socio-economic importance in the production of agave, two representative communities of the production systemsmentionedwereselected:ElCamarón,Yautepec and Matatlán, Tlacolula in Oaxaca. In order to get information, field trips were made, and by direct observation, the production systems and the natural environment were identified; also, community standards, peasant producers and selected communities. A random sample of 70 peasant farmers was obtained and a questionnaire was used to obtain information regarding farming activities used. The variables analyzed were: rest of the soil, rotation, intercropping and the use of agrochemicals. It was found that, there are changes in agricultural practices to be articulated into the emergence of the international market of tequila. In the agricultural systems in valleys, agricultural practices contribute to environmental conservation; however, in the system in hillsides conservation farming practices are not even performed.
Keywords: agriculture in valleys; ethnicity; hillside agriculture; mezcal agave; traditional technology